SIN A and COS A

Asked by sonali221994 | 13th Dec, 2009, 09:30: PM

Expert Answer:

sina and cos a are the roots of the given equation

sum of roots of the euation=-b/a

product of the roots =c/a

so

-b/a=sina +cosa

c/a=sinacosa

which gives,

b=-a(sina+cosa)

c=asinacosa

substitute these values in the LHS and RHS of the required equation and you will be able to prove it.

 

Answered by  | 14th Dec, 2009, 08:05: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.